Motives, meanings and way of human life: theoretical and historical reconstruction - Rubanau, Anatoly V. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
The article reveals the essence of motives and meanings of human life, reveals the mechanisms of their origin. The processes of the formation of meaning in an individual and the ways of accumulating universal meanings are considered. The historical dynamics of motives and meanings is analysed. The structure of the way of life is revealed and its relationship with motives and meanings is revealed. It is shown that the sources of motives and meanings are social status, belonging to a cultural tradition and self-reflection, self-development of individuals. The dynamism of these three factors determines the dynamic nature of motives, life meanings and typical forms of human activity.